Waktu Pembalikan Batang dan Dosis Pupuk Emulsi Ikan pada Pertumbuhan dan Hasil Tanaman Ubi Jalar (Ipomoea batatas L.) - Putri, Afina Tsaniya; Wirawati, Tutut; Setyaningrum , Tuti (Program Studi Agroteknologi INSTIPER, 2023)
Sweet potato is one of the carbohydrate producing food crops. Constraints in cultivation are determining the time of stem flip and the right dose of fish emulsion fertilizer in maintenance to increase sweet potato yields. This research aims to determine the time of stem flip, and dose of fish emulsion fertilizer on the growth and yield of sweet potato plants. The research method used is field experiments are arranged with a split plot design. The main plot was the stem flip time namely no flip, stem flip 4 and 8 WAP. The sub plot was the dose of fish emulsion fertilizer, namely without fish emulsion fertilizer, 120, 240, and 360 ml/plant. The data was analyzed using analysis of variance and Duncan’s Multiple Range Test with 5% level significancy. The results showed that the time of stem flip 8 WAP and the dose of fish emulsion fertilizer 360 ml/plant was the best combination for the number of viable tubers harvested of the plant and the weight of viable tubers harvested of the plant. The stem flip time of 8 WAP gave the best results on tuber weight of the plot, tuber weight of the hectare, and the total sugar content. The dose of fish emulsion fertilizer 360 ml/plant gave the best results on tuber weight of the plot and tuber weight of the hectare.